DFT study of reaction processes of methane combustion on PdO(1 0 0) - Dianat, Arezoo; Seriani, Nicola; Ciacchi, Lucio Colombi; Bobeth, Manfred; Cuniberti, Gianaurelio (Giovanni) (Chemical Physics, 2014)
The complex reaction mechanism of methane combustion on the PdO(1 0 0) surface is investigated within the framework of density functional theory. Driving forces and activation energies for the dissociative adsorption of methane and for the successive dehydrogenation of adsorbed hydrocarbons are calculated. Energy barriers of some of the dehydrogenation reactions are comparable to the barrier for the dissociative adsorption of methane, contrary to what is often assumed. Moreover, we find that reaction barriers for the early formation of C-O bonds are much lower than those for the complete dehydrogenation of CH4. In particular, reaction of oxygen molecules from the gas phase with suitable configurations of adsorbed H and CH3 can efficiently produce water and CH2O as oxidation products. Along this reaction path, the highest barrier is indeed given by the first dehydrogenation reaction.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Dehydrogenation; Density functional theory; Heterogeneous catalysis; Methane combustion